(untitled) (Experimental biology, 2016)
In the analysis of interaction between 2564 miRNAs with mRNAs of 185 genes, participating in the development of human myocardial infarction, there was identified 304 miRNAs binding sites with their mRNAs in 5’-UTR, CDS and 3’-UTR. For 54 miRNA involved in the development of human myocardial infarction, there was identified 17 target genes from 17510 genes. Five miRNA bind with mRNA of LRP1, LRP8 genes. Seven miRNA bind with mRNA of CYP1A2 and DNASE1 genes. Nine miRNA bind with mRNA of CCL5 and SP1 genes. mRNA of TFAM and SP1 genes have multiple binding sites with miR-466. mRNA of ADRB1 gene has multiple binding sites with miR-3960. mRNA of CD40LG, CDKN2B and IGF genes have multiple binding sites with miR-574-5р. The identified miR-762, has multiple binding sites with mRNA of CDKN1C. The unique miRNAs, having more than 300 binding sites is miR-619, miR-5095, miR-5096, miR-3960, miR-1322 and some miRNAs from miR-1273 family has binding sites in mRNA of many genes, participating in the development of myocardial infarction. miR-619-5р has 14 target genes, miR-5585-3p has 12 target genes, miR-5095 and miR-5096 have eight and six target genes. The family miR-1273a,c,d,e,f,g,h have 34 binding sites, including 19 binding sites of miR-1273g-3p in mRNA of 14 genes. The identified associations between miRNA and their target genes, which allow the use of it as diagnostic markers in myocardial infarction. As associations of miRNAs with target genes for diagnosis it is preferable to use associations of one miRNA with mRNA of several genes or multiple miRNA with the mRNA of one gene. The association of miR-149-3p with each of its target genes HNRNPA0, KCNJ6, MAP3K10, SHISA3 can be used for the diagnosis of MI. As candidates for the diagnosis recommended the associations of miR-619-5p with GSTCD and IL23R genes, having a ΔG/ΔGm value equal to 96%, and also associations of miR-4257 and C4B, miR-326 and NFKBIL1, miR-4300 and LAMA3 either having the ΔG/ΔGm value equal to 96%. The recommended associations of miRNA and mRNA of genes with high free energy of miRNA-mRNA interaction: miR-3960, miR-466, miR-574-5p together with their target genes pairs - PDE4D and SCAP, GSN and TNFSF4, CD40LG and OLR1. The unique miR-619-5p and miR-5095 have binding sites in mRNA of CCL5, DNASE1, F2R, IL6R, LDLR, MTHFR, STAT3, which is the basis for their use in diagnosis. The participation of miRNA of miR-1273 family necessary to control the expression of genes: ADIPOQ, CYP1A2, ENPP1, IGF1, KCNJ11, MEF2A, PPIA, TFAM. It is recommended miRNA and mRNA genes with a high value of the free energy of interaction at the binding sites. This pairs are miR-1273d, miR-4758-5p and miR-4763-5p binding with mRNA of PPIA, NFKB1 and SH2B1 genes. miR-1226-5p with mRNA of ALDH2 gene, miR-1183 with mRNA of THBS1 gene, and miR-6089-5p with mRNA of ADAM8, IL6R and TFAM genes.